Late childhood and adolescence growth sensitivity to political transition: the case of South African Cape Coloured schoolchildren during and post-apartheid - Bertens, Madelief G.B.C.; Ulijaszek, Stanley; Kozieł, Sławomir; Henneberg, Maciej (Anthropological Review, 2012)
South Africa underwent major social and economic change between 1987 and 1995. The release of Nelson Mandela in February 1990 proclaimed an end to the political system of apartheid, and the first freely elected non-White government in 1994 instigated social and economic reforms aimed at alleviating the consequences of apartheid. This paper aims to examine the impact of these socio-economic and political changes on height, weight and body mass index (BMI) in childhood and late adolescence. An analysis was carried out of longitudinal data of 258 urban and rural South African Cape Coloured schoolchildren (6–18 years old) across the transitional periods from apartheid between 1987 and 1990, to this transition between 1991 and 1993, and finally to post-apartheid between 1994 and 1995. The anthropometric measures were standardized into age independent Z-scores. Analyses of variance with repeated measures were conducted to examine the growth in height, weight and BMI across these periods. The results show a significant main effect of measurement periods on height, weight and BMI Z-scores. Across time, the subjects increased in overall size, height, weight and BMI. For all the anthropometric measures there was a significant interaction effect between measurement period and sex, but none between measurement period and SES. The average increase in height, weight and BMI across time differed significantly for girls and boys, the average z-scores being greater in girls than in boys. For boys, there was little difference in height, weight and BMI Z-scores according to SES, and little increase across periods. Girls were generally taller, heavier with greater BMI than boys, and their scores increased across the time periods. High SES girls were taller, heavier and had higher BMI than low SES girls. Across the measurement periods, BMI and weight somewhat converged between the high and low SES girls. In the discussion these differences reflecting social sex distinctions are addressed.